HISTORY OF CREATION AND STUDY OF MEDICAL DICTIONARIES - Avezova Yulduz (Prospects for innovative technologies in science and education, 2025)
This article discusses the history of the creation of medical dictionaries and their study from a linguistic point of view. It should be noted that the emergence of medical dictionaries appeared gradually, and they have reached their perfect appearance today. The implementation of research on medical dictionaries shows how important this field is.